Radiation Therapy Improves Survival Outcome in Pancreatic Adenocarcinoma: Comparison of a 15-Year Institutional Experience at the University of Nebraska Medical Center with SEER Data. (27th January 2014) - Baine, Michael J.; Lin, Chi
Abstract : Objectives . We examined the role of radiation therapy (RT) in pancreatic adenocarcinoma (PA) treatment through a 15-year retrospective analysis of patients treated at University of Nebraska Medical Center (UNMC) as well as those from the SEER database. Methods . A total of 561 patients diagnosed with PA at UNMC between 1995 and 2011 and 60, 587 patients diagnosed between 1995 and 2009 from the SEER were included. Examined prognostic factors for overall survival (OS) were age, gender, race, stage, year of diagnosis, and treatment with surgery, chemotherapy (CT), or RT. Time to death was plotted by Kaplan-Meier method. A Cox proportional hazards model was used to evaluate prognostic factors for OS. Results . The median OS was 7.3 and 5 months for patients from UNMC and the SEER database, respectively. A Cox model of patients from UNMC showed that RT was associated with improved OS (HR 0.77, P = 0.018 ) after adjusting for factors including age, race, gender, stage, year of diagnosis, having surgery, or having CT. Cox analysis of patients from the SEER showed similar results (HR 0.65, P < 0. 0001 ). Conclusions . RT confers an independent survival advantage in patients being treated for PA which is apparent both at UNMC and through SEER data.